Comprehensive management for miliary tuberculosis associated with schizoaffective disorder in an adolescent female: A case report - Wina, Djiu,; Irwanto, Irwanto; Setyoningrum, Retno Asih; Chafid, Arda Pratama Putra; Hapsari, Rika; Febriyana, Nining (Edelweiss Applied Science and Technology, 2025)
Adolescents are vulnerable to tuberculosis (TB), some with severe forms like miliary TB, due to biological, psychosocial, and environmental factors. Schizoaffective disorder, though rare, adds complexity to TB management, requiring a multidisciplinary approach. This report aims to describe the comprehensive management of a 17-year-old female with miliary TB, anti-tuberculosis drug-induced hepatotoxicity (ADIH), and schizoaffective disorder, emphasizing the interplay between infectious disease and mental health. A 17-year-old female presented with shortness of breath, chronic cough, prolonged fever, and weight loss. Diagnosed with miliary TB via GeneXpert MTB/RIF testing and imaging, she was treated with first-line anti-tuberculosis drugs. On day 12, the patient developed ADIH, necessitating temporary discontinuation of particular anti-tuberculosis drugs and gradual reintroduction of therapy. Concurrent psychological evaluations revealed schizoaffective disorder, managed with psychiatric medication and counseling. Over 12 months, the patient exhibited clinical and psychological improvements, supported by family involvement and environmental adjustments. Integrated medical and psychosocial strategies are required in managing complex TB cases. Addressing comorbid mental health conditions and fostering a supportive environment is crucial for optimizing outcomes. The findings highlight the comprehensive management of complex TB and schizoaffective disorder using pharmacological and psychological therapy.